The Effectiveness of Match Technique to Improve Students’ Vocabulary Mastery based on Gender - Via Destika (Journal Corner of Education, Linguistics, and Literature, 2022)
This research that belongs to quantitative research aims at finding the effectiveness of make a match technique to improve students’ vocabulary based on gender. The instrument given to the students was vocabulary in the context of a descriptive text. The subject of this research consisted of 25 students. This research only used experimental class for this research. The result of this research, there were significant improvement between pre-test and post-test score. The result obtained from sample T-test, it was found that the p value (0,000) was lower than 0.05 and t-observed (25.296) was higher than t-table (2.064).  While the result of differences score between female and male based on post test, the p value (.859) was higher than 0.05, there were not significant differences of vocabulary score between female and male. So, this technique make students interesting in teaching and learning vocabulary, this technique also helps students to understand about material easily.